COMPARISON BETWEEN USING AUTHENTIC SONG LYRICS AND PICTURES AS MEDIA TO TEACH STUDENTSâ€™ WRITING COMPETENCE OF NARRATIVE TEXT (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2014)
This final project is a quasi experimental research aiming at investigating any significant difference of studentsâ€™ achievement in writing narrative texts which are taught by using authentic song lyrics and the one who are taught by using pictures with an assumption that these media can help them to interpret the content of the course. The subjects of the study were the eleventh graders of Semarang State Senior High School 2 in the academic year of 2013/2014. There were two groups which were given different treatments. The first group was the experimental group consisting of 34 students that was taught by using â€œauthentic song lyricsâ€ as media and the second group was the control group consisting of 34 students that was taught by using â€œpicturesâ€. In conducting experimental research, there were two classes that were used, XI Natural Science Program 11 as the experimental group and XI Natural Science Program 9 as the control group. Both groups were given pre test, treatments, and post test. In analyzing the data, normality test, homogeneity test, and t-test were used. The results of the study showed that the â€œauthentic song lyricsâ€ media which was applied in creating narrative text gave contribution in helping them write narrative texts. The data proved that there was a significant difference between the experimental and the control group achievement. Based on the statistical analysis, it could be seen that the studentsâ€™ post-test in the experimental group was higher than the control group. The mean of the experimental group improved than the control group. The t-value for two means of post-test was 3.333; meanwhile the critical value at Î± = 5% was 2.035. It proved that there is significant difference between the experimental group which was given â€œauthentic song lyricsâ€ media and the control group which was given â€œpictureâ€. It can be concluded that the â€œauthentic song lyricsâ€ is more effective than â€œpicturesâ€ to help the students in writing narrative texts.